PENERAPAN MODEL PEMBELAJARAN INKUIRI TERBIMBING DALAM HASIL BELAJAR IPA SISWA KELAS V SD NEGERI BANGUNREJO - Erma Oktarina; Dian Samitra; Armi Yuneti (Primary Education Journal Silampari (PEJS), 2021)
This study aims to determine the learning outcomes of class V SD Negeri Bangunrejo after using the guided inquiry learning model significantly completely. The method used is a quantitative research method with a quasi-experimental research design in the one group pre-test and post-test group design. The sampling technique used was simple random sampling technique. The data collection technique used a test in the form of a description. Data analysis techniques consist of requirements analysis techniques and hypothesis testing. The technique of testing requirements analysis uses the normality test while the hypothesis used is the one-sample t-test. The results showed that the average pre-test was obtained 22.4 with a completeness percentage of 0% or no students who completed while the average post-test was 78.2 with a percentage of 100% completeness or all students completed. Obtained the value of t (12.22)> t table (1.699). The results of this study indicate that the learning outcomes of SD Negeri Bangunrejo students are significantly complete. Keywords: Application, Guided Inquiry Learning Model, Learning Outcomes.